ANALYSIS OF INSTAGRAM SOCIAL MEDIA USAGE IN INCREASING CONTENT REACH AND INTERACTION AT PT POS INDONESIA KCU BANDUNG IN 2024 - Sulthan Rafi Deevan Haryadi; Leni Cahyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines the phenomenon of using Instagram social media by PT. POS Indonesia KCU Bandung in 2024. The rapid development of Instagram social media as a promotional medium can increase the reach and interaction of a company. Even though Instagram can increase reach and interaction, based on field observations there are several things that pose challenges in optimal use of Instagram social media. The effectiveness of content strategy, social media management, performance measurement and human resources are challenges in optimizing Instagram to increase reach and interaction from the company to customers. The aim of this research is to analyze the use of Instagram social media in increasing the reach and interaction of content at PT POS Indonesia KCU Bandung in 2024. This study uses a qualitative approach through observation, documentation and in-depth interviews with the company's social media team and analysis of content published on Instagram . The data collected includes insight into the strategies used, challenges faced and perceptions of the effectiveness of social media in achieving company communication goals. The research results show that the use of Instagram at PT. Pos Indonesia KCU Bandung has been doing quite well in increasing the reach and interaction of content. However, there are several things that need to be improved, namely